Réponses

2014-02-14T09:38:57+01:00
Bonjour,

1) A = x²+2x+1
       = (x+1)²
 B =x²+2x+1-8x(x+1)
    = (x+1)² - 8x(x+1)
    = (x+1)(x+1) - 8x(x+1)
    = (x+1)[(x+1) - 8x]
    = (x+1)(x+1 - 8x)
    = (x+1)(-7x+1)

2) A= 16+8x+x²
      = (x + 4)²
B =(x+16)(x+4)-(16+8x+x²)
   = (x+16)(x+4) - (x+4)² 
   = (x+16)(x+4) - (x+4)(x+4)
   = (x+4)[(x+16) - (x+4)]
   = (x+4)(x+16 - x - 4)
   = (x+4)* 12
   = 12(x + 4)

c) A= 25x²-9
      = (5x)² - 3²
      = (5x + 3)(5x - 3)
B = (5x+3)(5x+9)-(25x²-9)
   = (5x+3)(5x+9)-(5x+3)(5x-3)
   = (5x+3)[(5x+9)-(5x-3)]
   = (5x+3)(5x+9-5x+3)
   = (5x+3)* 12
   = 12(5x+3)